Community Pharmacists Attitude Towards Professional Practice in Penang, Malaysia - Ali, Abdul Nazer; Shalini, Sivadasan; Yen, Ping Ng; K, Prajapati Sunil; Yee, Ru Seah; Jia, Ying Saw; Ee, Thing Tan; Ahmed, Nazer Zulfikar (Journal of Pharmacy Practice and Community Medicine)
Background: Community pharmacists are the health professionals most accessible to the public. Public visit community pharmacies for their daily health care needs. Thus, community pharmacists’ attitude towards professional practice is very important. Method: This was a prospective, cross sectional study, using pre-validated questionnaire containing five constructs and 37 items. Each question was given scores 1-5 which denote 1 for very low; 2 for low; 3 for moderate; 4 for high and 5 for very high. The completed questionnaires were analysed using SPSS version 22. Statistical significance for dichotomous data was assessed using chi- square test. Result: Among the 87 participants in managerial activities, 71 (81.6%) scored good, 14 (16.1%) scored moderate, 2 (2.3%) scored poor. In dispensing activities, 71 (81.6%) scored good, 14 (16.1%) scored moderate, 2 (2.3%) scored poor. In pharmaceutical care activities, 56 (64.4%) scored good, 24 (27.6%) scored moderate, 7 (8.1%) scored poor. In inter/intra professional activities, 48 (55.2%) scored good, 15 (17.2%) scored moderate and 24 (27.6%) scored poor. In public health activities, 62 (71.6%) scored good, 19 (21.8%) scored moderate and 6 (6.9%) scored poor whereas in maintenance of competency activities, 71 (81.6%) had scored good, 9 (10.3%) scored moderate and 7 (8.1%) scored poor. Conclusion: Majority of the respondents were having good attitudes towards managerial, dispensing and maintenance of competence activities. However, only minority of the respondents realized the importance of establishing professional relationship with doctors. Continuing education and training programs on professional practice would be one significant approach in equipping community pharmacists with the knowledge, skills and behaviour needed to expand their scope of practice and improving public healthcare outcomes.
Keywords: Attitude; Community pharmacy; Pharmacist; Professional practice; Malaysia